The impact of access to post-secondry education information on "rural origin" students' access to higher education: A case of three schools in Ntabamhlophe, Kwazule-Natal - Njoko, M.B. (South African Journal of Higher Education, 2019)
Inequalities in recruitment, enrolment, and throughput rates in higher education among different socio-economic classes in the democratic South Africa have remained challenging to reduce. Unpacking spatial differences in access to post-secondary education information can strengthen initiatives aimed at reducing such inequalities. Research on access to and success at post-secondary education has based the vulnerability of students from disadvantaged backgrounds heavily on financial constraints. Neglecting the issue of information or Higher Education knowledge which plays a very important role in decision making. It is a challenge for people from disadvantaged backgrounds to find their way through the inexplicable labyrinth of academic forms, financial aid applications, faculty handbooks and prospectuses. Even in Higher Education people have access to formal and informal resources of information. The formal resources which include guidance counsellors, college training in AP courses (in the case of USA), college handbooks and university open days are readily available at wealthier schools than the poorer ones. It is however the informal knowledge networks that really matter in preparing for Higher Education application and admission. This paper argues that the adoption of market-related strategies in student recruitment results in uninformed and underprepared learners about prospects and possibilities of educational options and opportunities. Hence later on they take longer to complete or even drop out.